Total Synthesis of Marine Cyclic Enol-Phosphotriester Salinipostin Compounds - Zhao, Mingliang; Wei, Xianfeng; Liu, Xuemeng; Dong, Xueyang; Yu, Rilei; Wan, Shengbiao; Jiang, Tao (Journal of Ocean University of China, 2018)
Due to their structural diversity and variety of biological activities, marine natural products have been the subject of extensive study. These compounds, especially phospholipid polycyclic aromatic hydrocarbons, have a wide range of pharmacological applications, including embedded DNA and central nervous system, anti-tumor, anti-virus, anti-parasite, anti-bacterial, and antithrombotic effects. Unfortunately, the insufficient drug sources have limited the development of these compounds. In this study, we isolated salinpostin compounds from a fermentation solution of marine-derived Salinospora sp., which has a common bicyclic enol-phosphotriester core framework, as well as potent and selective antimalarial activities against P. falciparum with EC 50 = 50 nmol L −1 . The chemical synthesis of these compounds in greater quantities is necessary for their use in bioactivity studies. Thus we explored a short route with high yields and mild reaction conditions, which can generate combinatorial libraries for drug discovery and lead optimization. We developed a new total synthesis method for six cyclic enol-phosphotriester salinipotin compounds and their diastereomers. For the total synthesis of cyclipostin P, we prepared cyclic enol-phosphotriester salinipostin compounds in 10 steps from a readily accessible starting material, 1,3-dihydroxyacetone, and obtained an overall yield of 1.29%. We fully characterized these compounds by proton nuclear magnetic resonance ( 1 H-NMR), carbon-13 NMR ( 13 C-NMR), and high-resolution mass spectrometry (HRMS) analyses, and found they coincide absolutely with the same compounds reported previously.